DESIGN OF CENTRAL AIR CONDITIONING SYSTEM FOR MIST TOWER BUILDING-2 - Noman, Mashruf Ahmad; Rafique, Maimuna Torsa; Toma, Prionkari Banik (DEPARTMENT OF MECHANICAL ENGINEERING MILITARY INSTITUTE OF SCIENCE AND TECHNOLOGY MIRPUR CANTONMENT, DHAKA - 1216, BANGLADESH, 2019)
At first we are thankful to the Almighty, for His blessings and for giving us the courage and enthusiasm accompanied by which we have completed the thesis successfully in due time. We specially thank and express our profound gratitude to our respected thesis supervisor, Prof Dr. Dipak Kanti Das for his constant & meticulous supervision, valuable suggestions and encouragement to carry out this thesis. With due respect, we are also grateful to our respected dean Brig Gen Md. Lutfor Rahman, EME as well as Lt Col Golam Saklayen, EME and Lt Cdr K M R Sadi, (E), BN. We express indebtedness to Shimanto Square authority, Bashundhara Group authority and Bangladesh Bank authority. Finally we would like to thank everybody who supported us in any respect for the completion of the thesis. It has been a marvelous experience to work with such an esteemed faculty to carry out this thesis under one of the most reputable engineering institution of Bangladesh.